Getting the most from online learning (Pfeiffer, 2004)
Getting the Most from Online Learning is a must-have resource that helps people, become better e-learners by showing them how to prepare for, participate in, and apply e-learning in all its variations. Written by the leaders in e-learning, this book is filled with practical ideas, suggestions, and information about a wide variety of topics including how to: Participate effectively in on-line learning experiences Contribute to and learn from discussion groups and chat rooms Handle e-learning peer evaluations Participate in online group projects In addition, the expert authors share their personal e-learning experiences and show how they have mastered the discipline of e-learning for themselves.